The Palace of Contemplating Departure - Saito, Brynn, 1981- (Book collections on Project MUSE., 2013)
This collection of poetry begins in a cityscape and ends "deep in the cloud-filled valley," traversing myriad terrains - both emotional and physical - as it weaves towards completion. From the bays of Denmark to the deserts of California, the poet gathers stories of sudden departures, forced removals, and the journeys chosen in between.